A Systematic Review and Meta-Analysis of Autoantibodies for Diagnosis and Prognosis in Patients With Chronic Inflammatory Demyelinating Polyradiculoneuropathy - Guo, Xiaoqian; Tang, Lisha; Huang, Qianyi; Tang, Xiangqi (Frontiers in Neuroscience, 2021)
Objectives: To review the available evidence on sensitivity and specificity of anti-NF155 antibody detection in diagnosing a specific subset of patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) and to calculate the frequencies of different autoantibodies to paranodal proteins. Background: Diagnosis of CIDP relies on clinical and neurophysiologic criteria and lacks useful diagnostic biomarkers. A subset of CIDP patients exhibit atypical clinical phenotypes and impaired response to conventional treatments. These patients were reported as having autoantibodies targeting paranodal protein neurofascin isoform 155 (NF155), contactin-1 (CNTN1), and contactin-associated protein-1 (CASPR1). Here, we conducted a meta-analysis to summarize evidence on the diagnostic and prognostic value of these autoantibodies, especially for anti-NF155 antibody. Methods: We searched the following electronic bibliographic databases: PubMed, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), and Web of Science. Eligible studies provided information to calculate the frequencies of anti-NF155 antibody and anti-CNTN1 antibody, the sensitivity and speciﬁcity of anti-NF155 antibody, and the incidence of improvement and deterioration among anti-NF155 antibody seropositive CIDP patients. Heterogeneity was assessed using Q and I2 statistics. Results: The pooled frequency of anti-NF155 autoantibody across 14 studies was 7% (95% confidence interval [CI]: 0.05 to 0.10) with high heterogeneity; the overall pooled sensitivity and speciﬁcity of anti-NF155 antibody for the diagnosis of a specific subgroup of CIDP patients were 0.45 (95% CI: 0.29–0.63) and 0.93 (95% CI: 0.86-0.97), respectively. Conclusions: For diagnosing of a specific subset of CIDP characterized by poor response to intravenous immunoglobulin (IVIg), we found a moderate sensitivity and a high specificity. The anti-NF155 antibody test should be used as a confirmatory test rather than a screening test.